The forgotten role of toxicodynamics: How habitat quality alters the mite, Oppia nitens, susceptibility to zinc, independent of toxicokinetics. (July 2019) - Jegede, Olukayode O.; Awuah, Kobby F.; Fajana, Hamzat O.; Owojori, Olugbenga J.; Hale, Beverley A.; Siciliano, Steven D.
Abstract: Soil habitat quality is thought to influence metal toxicity via changes in speciation and thereby toxicokinetics. Here, we assessed the toxicokinetic and toxicodynamic effects of habitat quality on mite, Oppia nitens when exposed to zinc (Zn) contaminated soils. Forty-seven soils were ranked into three habitat qualities; high, medium, and low based on biological reproduction of Folsomia candida, Enchytraeus crypticus, and Elymus lanceolatus . From the 47 soils, eighteen soils (comprising of six soils from each habitat quality) were randomly selected and dosed with field relevant concentrations of Zn. Mite survival and reproduction were assessed after 28 days. Total Zn, bioaccessible Zn, Zn bioavailability, Zn body burden, lactate dehydrogenase activity (LDH) and glucose-6-phosphate dehydrogenase (G6PDH) activities of the mites were determined. Zinc toxicity and potency were much less in the high compared to low quality soils and the mites in the high habitat quality soils tolerated higher zinc body burdens (2040 ± 130 μg/g b.w) than the lower habitat quality (1180 ± 310 μg/g b.w). Lower LDH activity (20 ± 2 μU mg −1 ) in the high quality soils compared to lower quality soils (50 ± 8 μU mg −1 ) suggested that there was less stress in the high habitat quality mites. Despite changes in speciation across habitat qualities, bioavailability of zinc was similar (∼20%) irrespective of habitat quality. Our results suggest that the influence of soil properties on survival is modulated by toxicodynamics rather than toxicokinetics. Restoring habitat quality may be more important for soil invertebrate protection than metal concentration at contaminated sites. Highlights: Habitat quality influenced Zn toxicity to mites through toxicodynamics rather than toxicokinetics. Potency and toxicity of Zn to mites were lower in high habitat quality soils than low habitat quality soils. Regardless of Zn speciation differences, Zn bioavailability was similar in all habitat qualities. Mites in higher habitat quality soils were less stressed than mites in the lower habitat quality soils.